ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS DALAM MENDUKUNG PENGENDALIAN INTERNAL KAS PADA PT AGRO SINERGI NUSANTARA ACEH BARAT - Dewi, Nurmala; Tiara, Shita; Wirananda, Henny Andriyani; Silalahi, Alistraja Dison; Ovami, Debbi Chyntia (UNIVERSITAS DHARMAWANGSA, 2025)
Rapid economic development significantly drives company growth. This makes the role of accounting increasingly decisive in decision making related to company operations. This study aims to determine how the cash receipt and disbursement accounting information system at PT Agro Sinergi Nusantara Aceh Barat can support the effectiveness of internal control. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The data used in this study are primary data conducted by direct interviews with financial employees at PT Agro Sinergi Nusantara Aceh Barat and secondary data obtained from reference books, scientific papers, documents, previous researchers or other reading materials related to this study. The results of the study indicate that the cash receipt accounting information system at PT Agro Sinergi Nusantara Aceh Barat has been designed with good internal control principles, such as the separation of functions between cash recipients and recorders, as well as the use of official documents such as proof of transfer and account mutations and the cash disbursement accounting information system at PT Agro Sinergi Nusantara Aceh Barat involves the stages of submission, verification, payment, to reporting via Accurate Online. However, this system still faces obstacles in terms of delays in returning cash disbursement receipts which causes recording errors because bookkeeping is done the day after payment This shows that internal control over cash disbursements has not been running optimally and requires improvement to support the company's financial accuracy, transparency and accountability.